Conversion of glycerol to methanol over copper and nickel supported on HZSM-5 zeolite by hydrothermal process - Nurul Syuhada Spalie, 1988-; Ramli Mat, supervisor; Tuan Amran Tuan Abdullah, supervisor; Fakulti Kejuruteraan Kimia (2013)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2013